2018
DOI: 10.1534/g3.118.200229
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Hif1 Histone Chaperone in Saccharomyces cerevisiae

Abstract: The Hif1 protein in the yeast Saccharomyces cerevisie is an evolutionarily conserved H3/H4-specific chaperone and a subunit of the nuclear Hat1 complex that catalyzes the acetylation of newly synthesized histone H4. Hif1, as well as its human homolog NASP, has been implicated in an array of chromatin-related processes including histone H3/H4 transport, chromatin assembly and DNA repair. In this study, we elucidate the functional aspects of Hif1. Initially we establish the wide distribution of Hif1 homologs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Attempts have been made to separate out pre- and post-import machineries through biochemical fractionation of the cytosolic fraction. However, a number of factors identified to be cytosolic in these studies have been found to be nuclear when probed in intact cells; namely NASP [15,18], ASF1 [19–21], HAT1 [22,23] and RbAp46 [15,24,25]. The reason for this discrepancy could lie in the soluble nature of these proteins, rapidly leaking into the cytosolic fraction upon common sub-cellular fractionation methods, with insoluble proteins, such as lamins and tubulin, being poor controls for reporting on such mixings [15,26].…”
Section: Histone Synthesis and Nuclear Importmentioning
confidence: 99%
“…Attempts have been made to separate out pre- and post-import machineries through biochemical fractionation of the cytosolic fraction. However, a number of factors identified to be cytosolic in these studies have been found to be nuclear when probed in intact cells; namely NASP [15,18], ASF1 [19–21], HAT1 [22,23] and RbAp46 [15,24,25]. The reason for this discrepancy could lie in the soluble nature of these proteins, rapidly leaking into the cytosolic fraction upon common sub-cellular fractionation methods, with insoluble proteins, such as lamins and tubulin, being poor controls for reporting on such mixings [15,26].…”
Section: Histone Synthesis and Nuclear Importmentioning
confidence: 99%
“…Asf1 co-purifies with NASP in human cells. Similar to their human counterparts, yeast Asf1 interacts with Hif1, and the interaction is likely mediated by histones H3/H4 [ 13 ]. The AP-MS data of the co-purification with Asf1-FZZ from vegetatively growing cells and conjugation cells revealed the interaction of Asf1 and Nrp1 in T. thermophila [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In S. cerevisiae, Hif1 interacts with H3/H4, histone acetyltransferase complex, chromatin assembly proteins, DNA replication-associated proteins, DNA damage response proteins, transcription regulation-related proteins, and RNA polymerase II transcriptional pre-initiation complex assembly [ 13 ]. Hif1 buffers displaced histones during transcription and makes them available for immediate chromatin reassembly.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence supports Asf1p functioning upstream of both CAF-1 and Rtt106p during DNA replication [ 4 , 19 25 , 28 30 ], and links between Asf1p and Hif1p during chromatin assembly have also been reported [ 40 , 41 , 42 , 61 ], but the distinct cellular functions of CAF-1, Rtt106p, and Hif1p have remained unclear. To evaluate their relationship and uncover distinct functions, we first examined silencing at the crippled HMR a e** locus ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%